Association between Serum Antibodies to Oral Microorganisms and Hyperglycemia in Adults. (August 2014) - Merchant, A.T.; Shrestha, D.; Chaisson, C.; Choi, Y.H.; Hazlett, L.J.; Zhang, J.
We conducted a cross-sectional analysis to evaluate the relationship between serum antibody titers against 19 selected oral microorganisms and measures of hyperglycemia in a large, nationally representative data set. The study population consisted of 7, 848 participants from the National Health and Nutrition Examination Survey III (1988-1994) who were at least 40 yrs old, with complete serum IgG antibody data against 19 oral microorganisms. The 19 antibody titers were grouped into 4 categories via cluster analysis—orange-red, yellow-orange, orange-blue, and red-green—named to reflect predominant antibody titers against microorganisms in Socransky's classification scheme for oral microbes. Linear regression models weighted for complex survey design were used in which fasting blood glucose, fasting insulin, and HbA1c were outcomes and antibody cluster scores were exposures, adjusting for potential confounders. Higher orange-red cluster scores were associated with increased hyperglycemia, while higher orange-blue cluster scores were related with decreased hyperglycemia. A 1-unit-higher orange-red cluster score was associated with 0.46 mg/dL higher fasting blood glucose ( p = .0038), and a 1-unit-higher orange-blue cluster score was associated with 0.34% lower HbA1c ( p = .0257). Groups of antibody titers against periodontal microorganisms were associated with hyperglycemia independent of known risk factors.